The Effectiveness of Leadership at the Imam Bonjol Padang College of Social and Political Sciences in Decision Making: Efektifitas Kepemimpinan di Sekolah Tinggi Ilmu Sosial dan Politik (STISIPOL) Imam Bonjol Padang dalam Pembuatan Keputusan - Vivi Puspita; Riri Putri Dika; Rangga Wenda Prinoya; Jendri Mulyadi (International Journal of Technology Vocational Education and Training, 2021)
This research is based on the phenomenon that the leader of STISIPOL Imam Bonjol Padang as a leader of the university is suspected of having weaknesses in the management of his institution both administratively and academically. This condition is a problem that must be overcome in anticipation of a better situation considering that educational institutions are producers of human resources. The research method is descriptive qualitative. Data were collected using triangulation techniques through field observations, interviews and documentation studies, sampling techniques with purposive snowball sampling. The results show that the weakness of the leadership can be seen from the level of education and the lack of initiatives needed for the development of high schools, it is necessary to increase communication skills, literacy, and organizational understanding to increase the effectiveness of leadership functions for institutions and a good academic culture for all academicians